MITIGASI SIAGA BENCANA GERAKANTANAH DENGAN PERANGKAT EARLY WARNING SYSTEM (EWS) DAERAH BUKIT MANYARAN PERMAI KECAMATAN GUNUNG PATI SEMARANG JAWA TENGAH - Purwanti, Fitri (Geological Engineering E-Journal, 2013)
Mass movement cause catastrophic losses are not small, in addition to loss of property is sometimes also cause human fatalities. Mass movement incident requires ongoing disaster relief efforts ( disaster management), includes a planned and organized effort embodied in a series of activities undertaken to eliminate ( minimize ) some or all of the harm or loss caused by the disaster, as well as avoiding the risk of disasters that might occur, so that the impact can be reduced, or minimized, even if it may be omitted ( Sutikno, 2001). One way is by providing early warning for areas prone to mass movement. Installation of monitoring early detection mass movement intended as a means of mitigation efforts in providing an early warning signal / beginning of the communities living around the disaster -prone areas in order to be able to evacuate mass movement early so as to minimize casualties in the event of disaster mass movement / landslides. Early warning tool is set on a sliding distance tolerance of 3 ( three ) mm, 6 ( six ) mm then 9 ( nine ) mm. The spacing can be changed according to the characteristics of each region .Observations were made by means of geological mapping which aims to determine the location of the geological conditions in the area of Perumahan Manyaran Bukit Permai, Gunungpati, Semarang and instalation tools of early warning system, by means of a sensor exstensiometer and rainfall. Mass movement type contained in the study area in the form creeping and views of fields including the landslides rotation (rotational slides) and by including the slow-motion speed (very slow). It is influenced by several factors such as claystone lithology of conditions including in the formation of the hoist. Mudstone properties are easy to inflate (expansive clay) caused the landslide .Early Warning System ( EWS ) is a device that consists of several components, such as modems, local monitoring engine, digital landslide meter, battery, solar panel, regulator, rain gauge, and ancillary equipment. Landslide EWS is a monitoring system that is specifically designed to detect events that preceded the landslide in time to issue a warning immediately and initiate mitigation measures .At research area is an area of vulnerability mass movement intermediate level, mitigation in accordance with the recommendation that the condition PerumahanÂ Manyaran Bukit Permai. Mass movement can tackle disaster in the following manner: 1. Manufacture of gabions in the northern part of the study area, intended as a buffer on the slopes, except that its happening mengihindari erosion on the creek bank. 2. Control of water channel function to minimize the water that goes into the surface. 3. Grouting with the aim of closing the open discontrution, cavities and holes in the layer intended to improve soil strength .